Integrated Plant Breeding Strategies for Harmony between Modern Agriculture Production and the Environment - João Carlos da Silva Dias (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
Producing enough food that is safe and nutritious is the biggest challenge for 2050 where the world population is estimated to be 9.2 billion. To feed these people, the total food production will have to increase 50% to 60%. Climate models predict that warmer temperatures and increases in the frequency and duration of drought during the next decades will have negative impact on crop growth and productivity. These new global challenges require an integrated agricultural and breeding agenda. Intensifying sustainability agro-ecosystems by producing more food with lower inputs, adapting agriculture to climate change, conserving biodiversity through its use, and making markets to work for the small farmers are needed to address the main issues of present time. Plant breeding has played a vital role in the successful development of modern agriculture. In order to cope with the complexity of the combined effects of challenges such as population increase, food security, food safety and human health, we need to reconsider the role of diversity in plant breeding in sustaining biological diversity. A continuous supply of high-quality crop germplasm is the key to develop climate-resilient, nutritious and productive cultivars. Global efforts are underway to develop breeding populations, by exploiting exotic germplasm including wild and weedy relatives. Advances in genomics, phenomics and bio-informatic resources have led to the deployment of several knowledge-intensive approaches to accelerate genetic gains in diverse food crops. Trait heritability, gene action, number of genes controlling the target trait(s), heterosis and genotype × environment interactions determine the breeding method to use. Conventional plant breeding will remain the backbone of crop improvement strategies. Genetic engineering has the potential to address some of the most challenging biotic constraints faced by farmers, which are not easily addressed through conventional plant breeding alone. Protective measures and laws, especially patenting, must be moderated to eliminate coverage so broad that it stifles innovation. They must be made less restrictive to encourage research and free flow of materials and information. An open source software system has the potential to increase breeding efficiency through data and code sharing, while open source seed systems should allow for continued seed saving, breeding, and seed exchange without restriction. Plant breeding can be a powerful tool to bring “harmony” between agriculture and the environment, but partnerships and cooperation are needed to make this a reality.